BERKENALAN DENGAN TASAWUF AL-GAZALI - Abdul Mun'im Amaly; Asep Rifqi Fuad (Jurnal Al Burhan, 2022)
The teachings of Sufism are contradictory teachings until now because many say that it is the teachings of Sufism that push us towards jumud. This paper aims to describe the actual teachings of Sufism in the view of Imam Gazali. This study uses a konsep analisis method by reviewing and analyzing the sources of books, turats, and scientific journals on Sufism, which the researchers then provide an interpretation of the data that has been. This study concludes that there are three core teachings of Islam, namely Islam, Iman, and Ihsan. From "Islam" "Science of Fiqh" was developed (Islamic Law), from "Faith" was developed "Science of Kalam" or "Science of Tawheed", and from "Ihsan" was developed, "Science of Sufism" was born. Imam Gazali is an encyclopedic Sufism figure, in the sense that he mastered various kinds of knowledge, especially Fiqh (including politics), U?ul Fiqh, Kalam, and Philosophy (including logic), but it turns out that the sciences that he views are very important and can satisfy spiritually. that, it turns out to only produce confusion in the spiritual. Then he from all knowledge and all facilities and high honor began to study Sufism, and it turns out that in Sufism al-Gazali found spiritual satisfaction. The essence of al-Gazali's Sufism teachings is an effort without the main teachings of religion, namely Islam, Faith, and Ihsan in the sense of without the Science of Fiqh, Science of Kalam, and Science of Sufism, and the essence of these three statements is Muhâlafat al-Nafs (Controlling Lust). The strategy for al-Gazali in achieving worldly and hereafter happiness is Mu?âlafat al-Nafs. He wrote this thesis in the book Ihya 'Ul?m al-Din.